PERUBAHAN MASYARAKAT MELAYU DI KOTA MEDAN: SUATU KAJIAN TENTANG TRADISI MEMBANGUN RUMAH TINGGAL - Azmi Azmi; Adek Cerah Kurnia Azis (Gorga : Jurnal Seni Rupa, 2021)
This research was conducted to prove the changes in Malay society by studying the tradition of building houses, in the city of Medan, North Sumatra. The study used a qualitative descriptive method with an ethnomethodology and ethnoscience design, using 10 research subjects on stilt houses. This research instrument uses documentation and interview techniques which comprehensively want to see the cultural phenomenon of the Malay community in the city of Medan, in relation to the tradition of building houses. The results of the data analysis technique used by the Miles and Huberman model show that the change in the shape of the traditional house is caused by the Malay traditional factor which provides openness and flexibility. The changes in the Malay community in the city of Medan have caused the elements of traditional culture to be lost, but it is better that there are new cultural aspects that arise. The phenomenon of cultural transformation of the Malay community so far has taken place according to a flexible framework of customary rules, in responding to changing times it is still acceptable. The implication of the research results is that in some cases there is a tendency that the houses referred to are types of houses on stilts typology I and II, as “traditional identities.” As for residential buildings, “modern identity” is a typology or style III stilt house, which is more varied, monumental and formal. Furthermore, in some buildings, it can be seen that traditional building structures are not integrated with modern structures. Impressed with the value of decorative or ornamental carvings tend to change a lot, especially those of sacred, mystical and religious value. In essence, the Malay tradition of traditional Malay formulates that there are: "three symbols" depicted in the house, namely: the status contained in the hierarchy of people's lives, position, space, and prohibition rules (tabu). Keywords: change, malay society, tradition.AbstrakPenelitian ini dilakukan untuk membuktikan perubahan masyarakat Melayu suatu kajian tradisi membangun rumah tinggal, di kota Medan Sumatera Utara. Penelitian memakai metode deskriptif kualitatif dengan desain etnometodologi dan etnosains, menggunakan subjek penelitian sebanyak 10 buah rumah panggung. Instrumen penelitian ini memakai teknik dokumentasi dan interview yang secara komprehensif ingin melihat fenomena budaya masyarakat Melayu di kota Medan, dalam kaitannya dengan tradisi membangun rumah tinggal. Hasil dari teknik analisis data yang digunakan model Miles dan Huberman menunjukkan bahwa perubahan bentuk rumah tinggal tradisional disebabkan oleh faktor adat Melayu yang memberikan keterbukaan dan keluwesan. Perubahan-perubahan masyarakat Melayu di kota Medan menyebabkan unsur-unsur budaya tradisi ada yang hilang, namun sebaiknya ada aspek budaya baru yang timbul. Fenomena transformasi budaya masyarakat Melayu selama ini berlangsung sesuai kerangka aturan adat  yang fleksibel, dalam menyikapi perubahan zaman masih bisa diterima. Implikasi dari hasil penelitian dalam beberapa kasus terlihat ada kecenderungan bahwa rumah tinggal yang dirujuk adalah jenis rumah panggung tipologi I dan II, sebagai “identitas tradisional.” Sedangkan untuk bangunan rumah tinggal “identitas modern” adalah rumah panggung tipologi atau langgam III, ini lebih variatif, monumental dan formal. Selanjutnya pada beberapa bangunan terlihat struktur bangunan tradisi tidak menyatu dengan bangunan struktur modern. Terkesan nilai ragam hias atau ukiran ornamen cenderung banyak perubahan terutama yang bernilai sakral, mistis dan religius. Pada hakekatnya tradisi Melayu adat Melayu merumuskan ada : ”tiga simbolik” yang tergambar dalam rumahnya yakni: status yang terdapat dalam hirarki kehidupan masyarakat, kedudukan, ruang,  dan peraturan larangan (tabu).Kata Kunci:perubahan, masyarakat melayu, tradisi.Authors:Azmi : Universitas Negeri MedanAdek Cerah Kurnia Azis : Universitas Negeri Medan References:Adenansyah, T. (1989). Butir-butir Sejarah Suku Melayu Pesisir Sumatera Timur. Medan: Yayasan Karya.Radcliffe-Brown, A. R. (2013). The andaman Islanders. Cambridge University Press.Effendy, Tenas dan Mudra, Al Mahyudin. (2004). Rumah Melayu Memangku Adat dan Menjemput Zaman. Yogyakarta : AdiCita.Geertz, C. (2005). Clifford Geertz by His Colleagues. USA: University of Chicago Press.Highhouse, S., Lievens, F., & Sinar, E. F. (2003). Measuring Attraction to Organizations. Educational and psychological Measurement, 63(6), 986-1001.Heidekrueger, P. I., Ninkovic, M., Heine-Geldern,A., Herter, F., & Broer, P. N. (2017). End to-end  Versus End-to-Side Anastomoses in Free Flap Reconstruction: Single Centre Experiences. Journal of plastic surgery and hand surgery, 51(5), 362-365.Marsden, J. E., & Hughes, T. J. (1994). Mathematical Foundations of Elasticity. New York: Courier Corporation.Husny, M. Lah. (1976). Bentuk Rumah Tradisional Melayu. Medan: BP Husny.Koentjaraningrat. (1980) Sejarah Teori Antropologi I. Jakarta: UI Press.Miles, Mathew, B.  dan Huberman, A. Michael. (1972). Analisa Data Kualitatif. Jakarta : UI Press.Pelly, Usman (2019)  Orang Melayu dalam Kehidupan Kota Medan, dalam “Tak Melayu Hilang di Bumi.  Medan: Casa Mesra.Tambunan, Syahfitri. (2015). Arsitektural Vernakuler dari Rumah Panggung Indonesia. www. Analisadaily.com (diakses tanggal 19 September 2020).Tabrani, Primadi. (1995). Belajar dari Sejarah dan Lingkungan. Bandung: Penerbit  Institut Teknologi Bandung.